2012
DOI: 10.2478/v10136-012-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic steatohepatitis: an overview including treatments with herbals as alternative therapeutics

Abstract: Non-alcoholic steatohepatitis (NASH), an under-recognized hepatic ailment with increasing prevalence, is fast emerging as the dark horse of hepatic related morbidity and mortality. Though introduced as a hepatic condition as early as 1980, detailed exploration of its causes, underlying mechanisms and therapeutics has largely remained an ignored or neglected field. Only recently, the focus of attention has gravitated towards an understanding of NASH as a pathological manifestation of significance and a search f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 134 publications
5
8
0
Order By: Relevance
“…As shown in Table (3), supplementation of silymarin (1g silymarin/kg body weight intragastrically) after induction of NAFLD to rats showed a significant (p<0.05) decrease in the serum lipid profile (cholesterol, triglycerides, free fatty acids & leptin) as well as hepatic total lipids and cholesterol levels associated with a significant increase occurred in the serum adiponectin levels through the whole -02 -experiment periods (One and two months). These results are in agreement with those of Hajiaghamohammadi et al (2012) and Thounaojam et al (2012). They reported that the supplementation of silymarin improves dyslipidemia and decreases oxidative stress.…”
Section: (2011); Hajiaghamohammadi Et Al (2012) Rahimi Et Al (2012)supporting
confidence: 92%
See 4 more Smart Citations
“…As shown in Table (3), supplementation of silymarin (1g silymarin/kg body weight intragastrically) after induction of NAFLD to rats showed a significant (p<0.05) decrease in the serum lipid profile (cholesterol, triglycerides, free fatty acids & leptin) as well as hepatic total lipids and cholesterol levels associated with a significant increase occurred in the serum adiponectin levels through the whole -02 -experiment periods (One and two months). These results are in agreement with those of Hajiaghamohammadi et al (2012) and Thounaojam et al (2012). They reported that the supplementation of silymarin improves dyslipidemia and decreases oxidative stress.…”
Section: (2011); Hajiaghamohammadi Et Al (2012) Rahimi Et Al (2012)supporting
confidence: 92%
“…These data may be attributed to the powerful of pharma-properties of silymarin which acts against the pro-oxidant products mainly through free radical scavenging and the ability to increase cellular GSH content; its ability to regulate membrane permeability and increase membrane stability in the presence of xenobiotic damage; its capacity to regulate nuclear expression through steroid-like effects and its inhibition of the transformation of stellate hepatocytes into myofibroblasts (which mediate the deposition of collagen fibers, leading to fibrosis and cirrhosis). These results are in agreement with those of Haddad et al Thounaojam et al (2012). Moreover, Saller et al (2007) recorded that insulin sensitivity was restored by silymarin treatment as suggested by normalized insulinemia and HOMA-IR, despite the continued intake of the NAFLDinducing high fructose/fat diet.…”
Section: -7 -supporting
confidence: 89%
See 3 more Smart Citations